Advances in Neuroinfectious Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Advances in therapy, outcome, and prediction of neurological infections published in the past year are reviewed from the University of Colorado Denver Health Sciences Center.